Dissociation in borderline personality disorder: recent experimental, neurobiological studies, and implications for future research and treatment - Krause-Utz, Annegret; Frost, Rachel; Chatzaki, Elianne; Winter, Dorina; Schmahl, Christian; Elzinga, Bernet M. (Current psychiatry reports, 2021)
The aim of this review article is to give an overview over recent experimental neurobiological research on dissociation in borderline personality disorder (BPD), in order to inform clinicians and to stimulate further research. First, we introduce basic definitions and models that conceptualize dissociation from a transdiagnostic perspective. Then, we discuss recent findings in BPD.
Gesehen am 11.10.2021